The development of early pioneer neurons in the annelid Malacoceros fuliginosus - Kumar, Suman (BMC Evol Biol, 2020)
BACKGROUND: Nervous system development is an interplay of many processes: the formation of individual neurons, which depends on whole-body and local patterning processes, and the coordinated growth of neurites and synapse formation. While knowledge of neural patterning in several animal groups is increasing, data on pioneer neurons that create the early axonal scaffold are scarce. Here we studied the first steps of nervous system development in the annelid Malacoceros fuliginosus. RESULTS: We performed a dense expression profiling of a broad set of neural genes. We found that SoxB expression begins at 4 h postfertilization, and shortly later, the neuronal progenitors can be identified at the anterior and the posterior pole by the transient and dynamic expression of proneural genes. At 9 hpf, the first neuronal cells start differentiating, and we provide a detailed description of axonal outgrowth of the pioneer neurons that create the primary neuronal scaffold. Tracing back the clonal origin of the ventral nerve cord pioneer neuron revealed that it is a descendant of the blastomere 2d (2d(221)), which after 7 cleavages starts expressing Neurogenin, Acheate-Scute and NeuroD. CONCLUSIONS: We propose that an anterior and posterior origin of the nervous system is ancestral in annelids. We suggest that closer examination of the first pioneer neurons will be valuable in better understanding of nervous system development in spirally cleaving animals, to determine the potential role of cell-intrinsic properties in neuronal specification and to resolve the evolution of nervous systems.